Pengaruh Pengetahuan, Sikap dan Persepsi Terhadap Perilaku Pencegahan Servisitis Pada Wanita Usia Subur Di Boyolali - Septiana Juwita; Niken Bayu Argaheni (STIKES dan AKZI Karya Husada Kediri, 2022)
Cervicitis is a non-specific genital infection in women of childbearing age. More than 37% cervicitis marked by mucopurulent fluid and inflammation of cervical epithelium usually occurs. More than 75% of women in the world will experience vaginal discharge at least 2 times in their lifetime. The purpose of this study was to determine the effect of knowledge, attitudes and perceptions in cervicitis prevention behavior in women of childbearing age in Boyolali. Analytical research design with a cross sectional approach using randomized sampling, questionnaires as a collection tool, the analysis used was univariate and bivariate with Spearman rank test. The result of knowledge has a very weak relationship strength to behavior (correlation coefficient = 0.40), attitudes have a very weak relationship strength to behavior (correlation coefficient = 0.129) and perception has a moderate relationship strength (correlation coefficient = 0.213). So, behavior towards cervical prevention is influenced by perception but is not always influenced by knowledge and attitudes.